QSAR Models Guided by Molecular Dynamics Applied to Human Glucokinase Activators - de Assis, Tamiris Maria; Gajo, Giovanna Cardoso; de Assis, Letícia Cristina; Garcia, Letícia Santos; Silva, Daniela Rodrigues; Ramalho, Teodorico Castro; da Cunha, Elaine Fontes Ferreira (Chemical biology & drug design, 2016)
In this study, quantitative structure-activity relationship studies which make use of molecular dynamics trajectories were performed on a set of 54 glucokinase protein activators. The conformations obtained by molecular dynamics simulation were superimposed according to the twelve alignments tested in a virtual three-dimensional box comprised of 2 Å cells. The models were generated by the technique that combines genetic algorithms and partial least squares. The best alignment models generated with a determination coefficient (r(2)) between 0.674 and 0.743 and cross-validation (q(2)) between 0.509 and 0.610, indicating good predictive capacity. The 4D-QSAR models developed in this study suggest novel molecular regions to be explored in the search for better glucokinase activators.
Keywords: aktivace enzymů; Glucokinase; kvantitativní vztahy mezi strukturou a aktivitou; Enzyme Activation; glukokinasa; lidé; simulace molekulární dynamiky; Quantitative Structure-Activity Relationship; Molecular Dynamics Simulation; Humans